Tomato Juice to Increase Haemoglobin Levels in Pregnant Women - Lusi Lestari; Tasya Furriha Khoerussabila (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2023)
Introduction: Anemia in pregnancy is a condition of a mother with a hemoglobin level below 11 gr/dl in the first and third trimesters, or a hemoglobin level of less than 10.5 gr/dl in the second trimester. In Indonesia, anemia is generally caused by iron deficiency. Iron deficiency anemia is anemia caused by a deficiency of iron, folic acid, and vitamin B12 due to inadequate intake or low availability of iron. Efforts that can be made to overcome the lack of iron intake in pregnant women are to regularly consume Fe tablets. The presence of side effects from Fe tablets and physiological changes during pregnancy may increase pregnant women's non-compliance in consuming Fe tablets. Non-compliance between pregnant women consuming Fe tablets can cause anemia in pregnant women. The source of iron is not only obtained from consuming iron (Fe) tablets. Pregnant women can get iron from various foods that contain iron, including tomatoes. Objective: This literature review aims  to examine further about giving tomato juice to increase hemoglobin levels in pregnant women. Method: The method used in writing this article is a review of research results related to giving tomato juice to increase hemoglobin levels in pregnant women. Result: Based on the articles that have been analyzed, it can be seen that giving tomato juice can increase hemoglobin levels in pregnant women with anemia.  Conclusion: Tomato juice can accelerate the absorption of iron and increase the production of red blood cells so that hemoglobin levels increase. Referring to these conclusions, pregnant women should consume tomato juice regularly.